Palace of Horticulture (Pacific Novelty Co.)
On verso: Designed by Bakewell & Brown, San Francisco. It covers over five acres and was constructed at a cost of nearly $350,000. One of the most comprehensive and elaborate collections of rare plants ever assembled as exhibited in this structure.